Diseño de un sistema de indicadores de producción - Guadalupe Moyano, Edmundo Rafael (2009)
In order to take a production or management decision in any kind of business, the company must have a clear understanding why they take those decisions. Nowadays, the companies under study doesn´t have the knowledge of their current situation, this lack of information that is generated in the production department causes in this area negative effects in its performance, from poor utilization of machine capacities, to total lack of knowledge of the machinery efficiency. The objective of this study is to establish an indicators system to the production department. The methodology covers the collect of information of the company in study, the transition of the company vision into department objectives, the indicator´s identification and the creation of a sheet in Excel that controls them. Once created the software, information is generated identifying the current situation of the production department, real values, goals to achieve and recommendations are presented.